Current progress in antivascular tumor therapy. Issue 10 (October 2017) - Ho, Yi-Ju; Wang, Tzu-Chia; Fan, Ching-Hsiang; Yeh, Chih-Kuang
Graphical Abstract: Highlights: Antivascular therapy targets immature vessels to alter tumor microenvironment. Vascular disrupting agents have been evaluated in clinical trials for various tumors. Combination therapy can compensate the rim effect of antivascular therapy. Acoustic methods of antivascular therapy provide local vascular disruption. Abstract : The tumor vasculature transports oxygen, nutrients and drugs for crucial roles in tumor therapy. Antivascular therapy directly targets existing tumor vessels to reduce blood perfusion and then inhibit tumor growth. Vascular disrupting agents and ultrasound-stimulated microbubble destruction use chemical toxicity and physical effect, respectively, to damage vascular endothelial cells for antivascular therapy. Moreover, antivascular therapy can break vessel wall barriers and change the tumor microenvironment to compensate for the limitations of conventional chemotherapy or radiotherapy. This review presents current progress and an overview of antivascular therapy, which can inform the development and application in cancer research. Teaser: This review presents current progress and an overview of antivascular therapy to inform its development and application in cancer research.